Thermal expansion resistant power cable

CN122898050APending Publication Date: 2026-10-13QIYUAN ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611049613.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]但在长期实际运行场景中,热伸缩问题始终是影响电力电缆服役可靠性的核心痛点:当电缆承载的负荷电流随用电峰谷动态波动,叠加环境温度变化,电缆内部的铜铝导体、交联聚乙烯绝缘层会同步发生热胀冷缩——铜导体的线膨胀系数达17×10-6/℃,而交联聚乙烯绝缘层的膨胀系数更是高达200×10-6/℃,两者形变不同步会在层间产生持续的剪切应力,这种持续周期性的应力作用,会引发电缆反复形变、金属护套疲劳、线路位移滑落,甚至造成接头失效、绝缘破损等严重故障,大幅缩短电缆服役寿命,成为制约大容量、长距离电力电缆可靠应用的核心瓶颈问题

Benefits of technology

[0021]本发明通过上述原料的协同作用,限制了分子链滑移与塑性流动,显著的提高了电力电缆的抗热伸缩性,具有突出的实际作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of power cables, and provides a heat-shrinkage-resistant power cable, wherein a modified polyethylene material is prepared from raw materials including the following components in parts by mass: low-density polyethylene 60-65 parts, ethylene-vinyl acetate copolymer 25-30 parts, linear low-density polyethylene 5-15 parts, modified fly ash 5-8 parts, cross-linking agent 3-5 parts, antioxidant 0.2-1 part, copper-resistant agent 0.1-0.5 part, carbon black 2-3 parts, zinc stearate 0.5-1 part, and stearic acid 0.1-0.5 part; the fly ash is acidified, mixed with a silane solution, and subjected to an amination reaction to obtain aminated fly ash; the aminated fly ash, acrylic cage-shaped poly-silsesquioxane, a solvent, and a catalyst are mixed and subjected to an addition reaction to obtain the modified polyethylene material. Through the synergistic effect of the above-mentioned raw materials, the heat-shrinkage resistance of the power cable is significantly improved by limiting the molecular chain slippage and plastic flow, and the application has outstanding practical effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable technology, and in particular to a power cable resistant to thermal expansion and contraction. Background Technology

[0002] Power cables are core infrastructure equipment supporting the efficient operation of modern energy systems. They bear the core function of safe, stable, and low-loss transmission of electrical energy. They are the "power blood vessels" that maintain the continuity of electricity consumption for production and daily life throughout society and ensure the reliable operation of new power systems. Their operating status is directly related to the safety resilience and power supply quality of the entire power grid. They are an indispensable core component in the construction of all energy infrastructure.

[0003] However, in long-term actual operation scenarios, thermal expansion and contraction remains a core pain point affecting the reliability of power cables: when the load current carried by the cable fluctuates dynamically with peak and off-peak electricity demand, coupled with changes in ambient temperature, the copper and aluminum conductors and cross-linked polyethylene insulation layer inside the cable will simultaneously undergo thermal expansion and contraction—the linear expansion coefficient of copper conductors reaches 17×10⁻⁶. -6 / ℃, while the coefficient of thermal expansion of cross-linked polyethylene insulation is as high as 200×10. -6 / ℃, the asynchronous deformation of the two will generate continuous shear stress between the layers. This continuous periodic stress will cause repeated deformation of the cable, fatigue of the metal sheath, line displacement and slippage, and even serious faults such as joint failure and insulation damage, which will greatly shorten the service life of the cable and become the core bottleneck problem restricting the reliable application of large-capacity and long-distance power cables.

[0004] Therefore, developing a power cable that can resist thermal expansion and contraction to eliminate various safety hazards caused by thermal expansion and contraction at the source has become a key technical problem that urgently needs to be solved in the current power cable industry. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects in the prior art and provide a thermally resistant power cable.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a modified polyethylene material prepared from raw materials comprising the following parts by weight: The ingredients are: 60-65 parts low-density polyethylene, 25-30 parts ethylene-vinyl acetate copolymer, 5-15 parts linear low-density polyethylene, 5-8 parts modified fly ash, 3-5 parts crosslinking agent, 0.2-1 part antioxidant, 0.1-0.5 parts copper inhibitor, 2-3 parts carbon black, 0.5-1 part zinc stearate, and 0.1-0.5 parts stearic acid.

[0007] Preferably, the method for preparing modified fly ash includes the following steps: (1) Acidified fly ash is mixed with silane solution to carry out an amination reaction to obtain amination fly ash; (2) The modified fly ash is obtained by mixing aminated fly ash, acrylic cage-shaped polysilsesquioxane, solvent and catalyst and carrying out an addition reaction.

[0008] Preferably, the particle size of fly ash in step (1) is 40~80μm; The acidified solution in step (1) is a hydrochloric acid solution with a concentration of 0.05~0.1M; The ratio of fly ash to hydrochloric acid solution is 1g: 8~10mL; In step (1), the acidification temperature is 50~60℃ and the time is 1~2h; The silane solution in step (1) contains KH-550, ethanol, and water; The volume ratio of KH-550, ethanol and water is 10~20:200~250:10~15; The pH of the silane solution is 4-5; In step (1), the ratio of fly ash to silane solution is 30~50g: 300~400mL; In step (1), the amination reaction is carried out at a temperature of 70-80℃ for 6-8 hours.

[0009] Preferably, the solvent in step (2) is tetrahydrofuran and the catalyst is triethylamine; In step (2), the ratio of amination of fly ash, acrylic cage-like polysilsesquioxane, solvent and catalyst is 5g: 3~5g: 100~150mL: 2~3mL; In step (2), the addition reaction is carried out at a temperature of 40-60℃ for 12-24 hours.

[0010] Preferably, the crosslinking agent comprises dicumyl peroxide and triallyl isocyanurate; The mass ratio of dicumyl peroxide to triallyl isocyanurate is 2~3:1~2; Antioxidants include antioxidant 1010 and antioxidant 168; The mass ratio of antioxidant 1010 to antioxidant 168 is 1:1~2; The copper inhibitor is N,N′-bis(β-naphthyl)-p-phenylenediamine.

[0011] The present invention also provides a method for preparing the modified polyethylene material, comprising the following steps: (a) Modified fly ash, carbon black, zinc stearate, stearic acid, antioxidant and copper inhibitor are mixed, and then the first part of ethylene-vinyl acetate copolymer is added for granulation to obtain masterbatch; (b) Low-density polyethylene, residual ethylene-vinyl acetate copolymer and linear low-density polyethylene are mixed and then added to masterbatch for secondary mixing; then crosslinking agent is added for tertiary mixing, and granulation is performed to obtain granules; (c) The granules are extruded and crosslinked sequentially to obtain the modified polyethylene material.

[0012] Preferably, the mixing temperature in step (a) is 90~100℃, the time is 10~15min, and the rotation speed is 200~300rpm; In step (a), the mass of the first portion of the ethylene-vinyl acetate copolymer is 40-45% of the total mass of the ethylene-vinyl acetate copolymer; The granulation temperature in step (a) is 130~135℃.

[0013] Preferably, the temperature for the secondary mixing in step (b) is 125~130℃; The temperature of the three mixing steps in step (b) is ≤85℃; The granulation temperature in step (b) is 120~135℃.

[0014] Preferably, the extrusion temperature in step (c) is 120~140℃; In step (c), the crosslinking temperature is 170~180℃, the pressure is 15~20MPa, and the time is 15~20min.

[0015] The present invention also provides the application of the modified polyethylene material in the protective layer of thermally expandable power cables.

[0016] This invention provides a modified polyethylene material, prepared from raw materials comprising the following parts by mass: 60-65 parts of low-density polyethylene, 25-30 parts of ethylene-vinyl acetate copolymer, 5-15 parts of linear low-density polyethylene, 5-8 parts of modified fly ash, 3-5 parts of crosslinking agent, 0.2-1 parts of antioxidant, 0.1-0.5 parts of copper inhibitor, 2-3 parts of carbon black, 0.5-1 parts of zinc stearate, and 0.1-0.5 parts of stearic acid; wherein the preparation process of the modified fly ash is as follows: acidified fly ash is mixed with a silane solution for an amination reaction to obtain amminated fly ash; the amminated fly ash, acrylic cage-like polysilsesquioxane, solvent, and catalyst are mixed for an addition reaction to obtain the modified fly ash. After acidification, fly ash can activate the silanols on its surface. The large number of silanols and aluminols provide reaction sites for subsequent grafting of coupling agents. KH-550 is hydrolyzed in a water / ethanol system to obtain silanol. The silanol forms hydrogen bonds with the hydroxyl groups on the fly ash surface. Under heating conditions, it undergoes dehydration condensation to form Si-O-Si covalent bonds, anchoring the amino groups on the fly ash surface. At this time, an acrylic cage-like polysilsesquioxane is introduced to undergo an addition reaction with the amino group, completing the combination of fly ash and acrylic cage-like polysilsesquioxane, thus obtaining a filler suitable for modified polyethylene.

[0017] This invention applies modified fly ash to polyethylene materials. Dicumyl peroxide decomposes in the vulcanization pipe to generate free radicals, which initiate the formation of covalent cross-links between the main chains of LDPE / EVA / LLDPE. The polyallylic groups of triallyl isocyanate participate in co-cross-linking to form bridge nodes, ultimately forming a three-dimensional network structure.

[0018] In POSS-coupled aminated fly ash, the POSS cage-like Si-O-Si cores, with nanoscale dimensions, disperse in the amorphous region of PE and act as nanoscale physical crosslinking points, effectively suppressing chain segment slippage. Fly ash, as micron-sized inorganic rigid particles, provides macroscale high-temperature rigid support in the composite material; the rigid cores of fly ash bear part of the shear stress, inhibiting high-temperature creep of the matrix, and forming a "macro-micro" dual-scale reinforcement with the POSS nano-anchors.

[0019] The acetate side groups of EVA and the amino / amide bonds on the modified fly ash surface exhibit hydrogen bonding and dipole-dipole interactions, improving the dispersibility of inorganic fillers in the PE matrix and reducing agglomeration and interfacial defects. A good interface means that stress can be uniformly transferred to the crosslinking network and POSS anchor points, avoiding early deformation or fracture caused by localized stress concentration.

[0020] Antioxidants capture free radicals during the material's service life, preventing cross-linking bond breakage and oxidative degradation, thereby maintaining long-term thermal expansion resistance; copper inhibitors specifically inhibit oxidative degradation catalyzed by copper conductors, protecting the sheath layer close to the conductor.

[0021] This invention, through the synergistic effect of the aforementioned raw materials, restricts molecular chain slippage and plastic flow, significantly improving the thermal expansion and contraction resistance of power cables, and has outstanding practical effects. Detailed Implementation

[0022] This invention provides a modified polyethylene material prepared from raw materials comprising the following parts by weight: The ingredients are: 60-65 parts low-density polyethylene, 25-30 parts ethylene-vinyl acetate copolymer, 5-15 parts linear low-density polyethylene, 5-8 parts modified fly ash, 3-5 parts crosslinking agent, 0.2-1 part antioxidant, 0.1-0.5 parts copper inhibitor, 2-3 parts carbon black, 0.5-1 part zinc stearate, and 0.1-0.5 parts stearic acid.

[0023] In this invention, the mass fraction of low-density polyethylene is preferably 60.5 to 64.5 parts, more preferably 61 to 64 parts, and even more preferably 62 to 63 parts.

[0024] In this invention, the mass fraction of the ethylene-vinyl acetate copolymer is preferably 25.5 to 29.5 parts, more preferably 26 to 29 parts, and even more preferably 27 to 28 parts.

[0025] In this invention, the mass fraction of linear low-density polyethylene is preferably 6 to 14 parts, more preferably 7 to 13 parts, and even more preferably 8 to 12 parts.

[0026] In this invention, the modified fly ash is preferably 5.5 to 7.5 parts by mass, more preferably 6 to 7 parts, and even more preferably 6.4 to 6.6 parts by mass.

[0027] In this invention, the mass fraction of the crosslinking agent is preferably 3.5 to 4.5 parts, more preferably 3.6 to 4.4 parts, and even more preferably 3.8 to 4.2 parts.

[0028] In this invention, the antioxidant is preferably 0.3 to 0.9 parts by mass, more preferably 0.4 to 0.8 parts, and even more preferably 0.5 to 0.7 parts by mass.

[0029] In this invention, the mass fraction of the copper-resistant agent is preferably 0.15 to 0.45 parts, more preferably 0.2 to 0.4 parts, and even more preferably 0.25 to 0.35 parts.

[0030] In this invention, the mass fraction of carbon black is preferably 2.1 to 2.9 parts, more preferably 2.2 to 2.8 parts, and even more preferably 2.4 to 2.6 parts.

[0031] In this invention, the preferred mass fraction of zinc stearate is 0.6 to 0.9 parts, more preferably 0.7 to 0.8 parts, and even more preferably 0.75 to 0.78 parts.

[0032] In this invention, the mass fraction of stearic acid is preferably 0.15 to 0.45 parts, more preferably 0.2 to 0.4 parts, and even more preferably 0.25 to 0.35 parts.

[0033] In this invention, the method for preparing modified fly ash includes the following steps: (1) Acidified fly ash is mixed with silane solution to carry out an amination reaction to obtain amination fly ash; (2) The modified fly ash is obtained by mixing aminated fly ash, acrylic cage-shaped polysilsesquioxane, solvent and catalyst and carrying out an addition reaction.

[0034] In this invention, the particle size of fly ash in step (1) is preferably 40~80μm, more preferably 50~70μm, and even more preferably 55~65μm.

[0035] In this invention, the acidified solution in step (1) is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is preferably 0.05~0.1M, more preferably 0.06~0.09M, and even more preferably 0.07~0.08M.

[0036] In this invention, the preferred ratio of fly ash to hydrochloric acid solution is 1g:8~10mL, more preferably 1g:8.5~9.5mL, and even more preferably 1g:9~9.2mL.

[0037] In this invention, the acidification temperature in step (1) is preferably 50~60℃, more preferably 52~58℃, and even more preferably 54~56℃; the time is preferably 1~2h, more preferably 1.2~1.8h, and even more preferably 1.4~1.6h; stirring is maintained during the acidification process.

[0038] In this invention, after acidification, the product is washed until neutral and dried to constant weight.

[0039] In this invention, the silane solution in step (1) contains KH-550, ethanol and water.

[0040] In this invention, the volume ratio of KH-550, ethanol and water is preferably 10~20:200~250:10~15, more preferably 12~18:210~240:11~14, and even more preferably 14~16:220~230:12~13.

[0041] In this invention, the pH of the silane solution is preferably 4-5, more preferably 4.2-4.8, and even more preferably 4.4-4.6, and glacial acetic acid is used to adjust the pH.

[0042] In this invention, the preferred ratio of fly ash to silane solution in step (1) is 30~50g:300~400mL, more preferably 35~45g:320~380mL, and even more preferably 38~42g:340~360mL.

[0043] In this invention, the temperature of the amination reaction in step (1) is preferably 70~80℃, more preferably 72~78℃, and even more preferably 74~76℃; the time is preferably 6~8h, more preferably 6.5~7.5h, and even more preferably 6.8~7.2h; the rotation speed is preferably 300~400rpm, more preferably 320~380rpm, and even more preferably 340~360rpm.

[0044] In this invention, after the amination reaction in step (1) is completed, the mixture is filtered, washed with ethanol, and dried to constant weight. The drying temperature is preferably 100~110℃, more preferably 102~108℃, and even more preferably 104~106℃. After drying, amination-treated fly ash is obtained.

[0045] In this invention, the solvent in step (2) is tetrahydrofuran and the catalyst is triethylamine.

[0046] In this invention, the preferred ratio of the amount of aminated fly ash, acrylic cage-like polysilsesquioxane, solvent and catalyst in step (2) is 5g:3~5g:100~150mL:2~3mL, more preferably 5g:3.5~4.5g:110~140mL:2.2~2.8mL, and even more preferably 5g:3.8~4.2g:120~130mL:2.4~2.6mL.

[0047] In this invention, the addition reaction in step (2) is carried out in a protective atmosphere, which is nitrogen, helium or neon.

[0048] In this invention, the temperature of the addition reaction in step (2) is preferably 40~60℃, more preferably 45~55℃, and even more preferably 48~52℃; the time is preferably 12~24h, more preferably 15~20h, and even more preferably 17~18h.

[0049] In this invention, after the addition reaction in step (2) is completed, the mixture is filtered, washed sequentially with tetrahydrofuran and ethanol, and dried to constant weight. The drying temperature is preferably 40~45℃, more preferably 41~44℃, and even more preferably 42~43℃. After drying, modified fly ash is obtained.

[0050] In this invention, the crosslinking agent comprises dicumyl peroxide and triallyl isocyanate.

[0051] In this invention, the mass ratio of dicumyl peroxide to triallyl isocyanate is preferably 2~3:1~2, more preferably 2.2~2.8:1.2~1.8, and even more preferably 2.4~2.6:1.4~1.6.

[0052] In this invention, the antioxidants include antioxidant 1010 and antioxidant 168.

[0053] In this invention, the mass ratio of antioxidant 1010 to antioxidant 168 is preferably 1:1 to 2, more preferably 1:1.2 to 1.8, and even more preferably 1:1.4 to 1.6.

[0054] In this invention, the copper inhibitor is N,N′-bis(β-naphthyl)-p-phenylenediamine.

[0055] The present invention also provides a method for preparing the modified polyethylene material, comprising the following steps: (a) Modified fly ash, carbon black, zinc stearate, stearic acid, antioxidant and copper inhibitor are mixed, and then the first part of ethylene-vinyl acetate copolymer is added for granulation to obtain masterbatch; (b) Low-density polyethylene, residual ethylene-vinyl acetate copolymer and linear low-density polyethylene are mixed and then added to masterbatch for secondary mixing; then crosslinking agent is added for tertiary mixing, and granulation is performed to obtain granules; (c) The granules are extruded and crosslinked sequentially to obtain the modified polyethylene material.

[0056] In this invention, the mixing temperature in step (a) is preferably 90~100℃, more preferably 92~98℃, and even more preferably 94~96℃; the mixing time is preferably 10~15min, more preferably 11~14min, and even more preferably 12~13min; the mixing speed is preferably 200~300rpm, more preferably 220~280rpm, and even more preferably 240~260rpm.

[0057] In this invention, the mass of the first portion of the ethylene-vinyl acetate copolymer in step (a) is preferably 40-45% of the total mass of the ethylene-vinyl acetate copolymer, more preferably 41-44%, and even more preferably 42-43%.

[0058] In this invention, the granulation temperature in step (a) is preferably 130~135°C, more preferably 131~134°C, and even more preferably 132~133°C.

[0059] In this invention, the temperature of the secondary mixing in step (b) is preferably 125~130°C, more preferably 126~129°C, and even more preferably 127~128°C.

[0060] In this invention, the temperature of the three mixing steps in step (b) is preferably ≤85°C, more preferably ≤80°C, and even more preferably ≤75°C.

[0061] In this invention, the granulation temperature in step (b) is preferably 120~135°C, more preferably 125~130°C, and even more preferably 128~129°C.

[0062] In this invention, the extrusion temperature in step (c) is preferably 120~140°C, more preferably 125~135°C, and even more preferably 128~132°C.

[0063] In this invention, the crosslinking temperature in step (c) is preferably 170~180℃, more preferably 172~178℃, and even more preferably 174~176℃; the pressure is preferably 15~20MPa, more preferably 16~19MPa, and even more preferably 17~18MPa; and the time is preferably 15~20min, more preferably 15~20min, and even more preferably 15~20min.

[0064] The present invention also provides the application of the modified polyethylene material in the protective layer of thermally expandable power cables.

[0065] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0066] Example 1

[0067] Prepare the following proportions of raw materials by weight: 62 parts low-density polyethylene, 28 parts ethylene-vinyl acetate copolymer, 11 parts linear low-density polyethylene, 6 parts modified fly ash, 4 parts crosslinking agent, 0.8 parts antioxidant, 0.2 parts copper inhibitor N,N′-bis(β-naphthyl)-p-phenylenediamine, 2.5 parts carbon black N330, 0.8 parts zinc stearate, and 0.4 parts stearic acid.

[0068] The preparation process of modified fly ash is as follows: Fly ash with a particle size of 60 μm was placed in a 0.08 M hydrochloric acid solution at a ratio of 1 g fly ash: 9 mL hydrochloric acid solution. After mixing, the mixture was stirred at 55 °C for 1.5 h. After acidification, the solid was obtained by filtration, washed until neutral, and dried to constant weight. KH-550, ethanol, and water were mixed at a volume ratio of 15:230:14, and the pH was adjusted to 4.5 with glacial acetic acid to obtain a silane solution. The ratio of fly ash to silane solution was controlled at 40 g: 350 mL, and the mixture was reacted at 75 °C and 350 rpm for 7 h. After the reaction, the mixture was filtered, washed with ethanol, and dried at 100 °C to constant weight to obtain aminated fly ash. Aminated fly ash, acrylic cage-like polysilsesquioxane, tetrahydrofuran, and triethylamine were mixed in a ratio of 5 g: 4 g: 120 mL: 2.5 mL and reacted at 50 °C for 20 h under a nitrogen atmosphere. After the reaction was completed, the mixture was filtered, washed sequentially with tetrahydrofuran and ethanol, and dried at 40 °C to constant weight to obtain modified fly ash.

[0069] The mass ratio of dicumyl peroxide to triallyl isocyanate in the crosslinking agent is 2.5:1.5.

[0070] The mass ratio of antioxidant 1010 to antioxidant 168 in the antioxidant is 1:1.5.

[0071] Modified fly ash, carbon black, zinc stearate, stearic acid, antioxidant, and copper inhibitor are mixed at 95°C and stirred at 250 rpm for 15 minutes. Then, the first part of the ethylene-vinyl acetate copolymer (preferably 42% of the total mass of the ethylene-vinyl acetate copolymer) is added, and granulation is carried out at 130°C to obtain masterbatch.

[0072] Low-density polyethylene, residual ethylene-vinyl acetate copolymer and linear low-density polyethylene are mixed and then added to masterbatch for secondary mixing at 125°C; then a crosslinking agent is added and the temperature is lowered to 80°C for tertiary mixing, and granulation is carried out at 125°C to obtain granules.

[0073] The granules were extruded at 130°C to obtain flakes, and then vulcanized at 175°C and 18MPa for 15 minutes to complete crosslinking and obtain modified polyethylene material.

[0074] Example 2

[0075] Prepare the following proportions of raw materials by weight: 65 parts low-density polyethylene, 25 parts ethylene-vinyl acetate copolymer, 7 parts linear low-density polyethylene, 8 parts modified fly ash, 3 parts crosslinking agent, 1 part antioxidant, 0.4 parts copper inhibitor N,N′-bis(β-naphthyl)-p-phenylenediamine, 2.3 parts carbon black N330, 1 part zinc stearate, and 0.1 parts stearic acid.

[0076] The preparation process of modified fly ash is as follows: Fly ash with a particle size of 50 μm was placed in a 0.1 M hydrochloric acid solution at a ratio of 1 g fly ash to 8 mL hydrochloric acid solution. After mixing, the mixture was stirred at 50 °C for 2 h. After acidification, the solid was obtained by filtration, washed until neutral, and dried to constant weight. KH-550, ethanol, and water were mixed at a volume ratio of 10:250:15, and the pH was adjusted to 4 using glacial acetic acid to obtain a silane solution. The ratio of fly ash to silane solution was controlled at 30 g:300 mL, and the mixture was reacted at 70 °C and 400 rpm for 8 h. After the reaction, the mixture was filtered, washed with ethanol, and dried at 100 °C to constant weight to obtain aminated fly ash. Aminated fly ash, acrylic cage-like polysilsesquioxane, tetrahydrofuran, and triethylamine were mixed in a ratio of 5 g: 3 g: 110 mL: 3 mL and reacted at 40 °C for 12 h under a nitrogen atmosphere. After the reaction was completed, the mixture was filtered, washed sequentially with tetrahydrofuran and ethanol, and dried at 45 °C to constant weight to obtain modified fly ash.

[0077] The mass ratio of dicumyl peroxide to triallyl isocyanate in the crosslinking agent is 3:1.

[0078] The mass ratio of antioxidant 1010 to antioxidant 168 in the antioxidant is 1:2.

[0079] Modified fly ash, carbon black, zinc stearate, stearic acid, antioxidant, and copper inhibitor are mixed at 90°C and stirred at 200 rpm for 10 minutes. Then, the first part of the ethylene-vinyl acetate copolymer (preferably 40% of the total mass of the ethylene-vinyl acetate copolymer) is added, and the mixture is granulated at 135°C to obtain masterbatch.

[0080] Low-density polyethylene, residual ethylene-vinyl acetate copolymer and linear low-density polyethylene are mixed and then added to masterbatch for secondary mixing at 130°C; then a crosslinking agent is added and the temperature is lowered to 85°C for tertiary mixing, and granulation is carried out at 135°C to obtain granules.

[0081] The granules were extruded at 140°C to obtain flakes, and then vulcanized at 172°C and 17MPa for 18 minutes to complete crosslinking and obtain modified polyethylene material.

[0082] Example 3

[0083] Prepare the following proportions of raw materials by weight: 61 parts low-density polyethylene, 30 parts ethylene-vinyl acetate copolymer, 14 parts linear low-density polyethylene, 6 parts modified fly ash, 5 parts crosslinking agent, 0.3 parts antioxidant, 0.1 parts copper inhibitor N,N′-bis(β-naphthyl)-p-phenylenediamine, 3 parts carbon black N330, 0.5 parts zinc stearate, and 0.5 parts stearic acid.

[0084] The preparation process of modified fly ash is as follows: Fly ash with a particle size of 70 μm was placed in a 0.05 M hydrochloric acid solution at a ratio of 1 g fly ash: 10 mL hydrochloric acid solution. After mixing, the mixture was stirred at 60 °C for 2 h. After acidification, the solid was obtained by filtration, washed until neutral, and dried to constant weight. KH-550, ethanol, and water were mixed at a volume ratio of 18:210:11, and the pH was adjusted to 4.8 using glacial acetic acid to obtain a silane solution. The ratio of fly ash to silane solution was controlled at 50 g: 390 mL, and the mixture was reacted at 80 °C and 320 rpm for 6 h. After the reaction, the mixture was filtered, washed with ethanol, and dried at 100 °C to constant weight to obtain aminated fly ash. Aminated fly ash, acrylic cage-like polysilsesquioxane, tetrahydrofuran, and triethylamine were mixed in a ratio of 5 g: 4.8 g: 140 mL: 2.3 mL and reacted at 55 °C for 22 h under a nitrogen atmosphere. After the reaction was completed, the mixture was filtered, washed sequentially with tetrahydrofuran and ethanol, and dried at 45 °C to constant weight to obtain modified fly ash.

[0085] The mass ratio of dicumyl peroxide to triallyl isocyanate in the crosslinking agent is 2:1.8.

[0086] The mass ratio of antioxidant 1010 to antioxidant 168 in the antioxidant is 1:1.5.

[0087] Modified fly ash, carbon black, zinc stearate, stearic acid, antioxidant, and copper inhibitor are mixed at 100°C and stirred at 300 rpm for 15 minutes. Then, the first part of the ethylene-vinyl acetate copolymer (preferably 45% of the total mass of the ethylene-vinyl acetate copolymer) is added, and granulation is carried out at 130°C to obtain masterbatch.

[0088] Low-density polyethylene, residual ethylene-vinyl acetate copolymer and linear low-density polyethylene are mixed and then added to masterbatch for secondary mixing at 125°C; then a crosslinking agent is added and the temperature is lowered to 85°C for tertiary mixing, and granulation is carried out at 130°C to obtain granules.

[0089] The granules were extruded at 120°C to obtain flakes, and then vulcanized at 178°C and 20MPa for 20 minutes to complete crosslinking and obtain modified polyethylene material.

[0090] The modified polyethylene materials prepared in Examples 1-3 were subjected to performance tests. The tensile strength and elongation at break were determined according to GB / T 1040.2-2022, and the thermal elongation was determined according to JB / T 10437-2004. The results are recorded in Table 1.

[0091] Table 1 Performance Test Results

[0092] As can be seen from Table 1, the modified polyethylene material provided by this invention has excellent thermal elongation performance while ensuring conventional mechanical properties. It solves the problem that traditional polyethylene materials are prone to thermal deformation and excessive permanent elongation under high temperature conditions. Even under extreme high temperature conditions of cable overload operation, it can maintain stable dimensional shape and will not have problems such as insulation layer bulging or displacement. It is fully compatible with the actual operating scenarios of power cables and can be directly applied to a full range of power cable products from low-voltage distribution networks to high-voltage transmission networks, which can significantly extend the service life of cables and reduce the risk of line maintenance failures.

[0093] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A modified polyethylene material, characterized in that, It is prepared from raw materials comprising the following parts by mass: The ingredients are: 60-65 parts low-density polyethylene, 25-30 parts ethylene-vinyl acetate copolymer, 5-15 parts linear low-density polyethylene, 5-8 parts modified fly ash, 3-5 parts crosslinking agent, 0.2-1 part antioxidant, 0.1-0.5 parts copper inhibitor, 2-3 parts carbon black, 0.5-1 part zinc stearate, and 0.1-0.5 parts stearic acid.

2. The modified polyethylene material as described in claim 1, characterized in that, The preparation method of modified fly ash includes the following steps: (1) Acidified fly ash is mixed with silane solution to carry out an amination reaction to obtain amination fly ash; (2) The modified fly ash is obtained by mixing aminated fly ash, acrylic cage-shaped polysilsesquioxane, solvent and catalyst and carrying out an addition reaction.

3. The modified polyethylene material as described in claim 2, characterized in that, In step (1), the particle size of fly ash is 40~80μm; The acidified solution in step (1) is a hydrochloric acid solution with a concentration of 0.05~0.1M; The ratio of fly ash to hydrochloric acid solution is 1g: 8~10mL; In step (1), the acidification temperature is 50~60℃ and the time is 1~2h; The silane solution in step (1) contains KH-550, ethanol, and water; The volume ratio of KH-550, ethanol and water is 10~20:200~250:10~15; The pH of the silane solution is 4-5; In step (1), the ratio of fly ash to silane solution is 30~50g: 300~400mL; In step (1), the amination reaction is carried out at a temperature of 70-80℃ for 6-8 hours.

4. The modified polyethylene material as described in claim 3, characterized in that, In step (2), the solvent is tetrahydrofuran and the catalyst is triethylamine; In step (2), the ratio of amination of fly ash, acrylic cage-like polysilsesquioxane, solvent and catalyst is 5g: 3~5g: 100~150mL: 2~3mL; In step (2), the addition reaction is carried out at a temperature of 40-60℃ for 12-24 hours.

5. The modified polyethylene material as described in claim 4, characterized in that, The crosslinking agents include dicumyl peroxide and triallyl isocyanurate; The mass ratio of dicumyl peroxide to triallyl isocyanurate is 2~3:1~2; Antioxidants include antioxidant 1010 and antioxidant 168; The mass ratio of antioxidant 1010 to antioxidant 168 is 1:1~2; The copper inhibitor is N,N′-bis(β-naphthyl)-p-phenylenediamine.

6. A method for preparing the modified polyethylene material according to any one of claims 1 to 5, characterized in that, Includes the following steps: (a) Modified fly ash, carbon black, zinc stearate, stearic acid, antioxidant and copper inhibitor are mixed, and then the first part of ethylene-vinyl acetate copolymer is added for granulation to obtain masterbatch; (b) Low-density polyethylene, residual ethylene-vinyl acetate copolymer and linear low-density polyethylene are mixed and then added to masterbatch for secondary mixing; then crosslinking agent is added for tertiary mixing, and granulation is performed to obtain granules; (c) The granules are extruded and crosslinked sequentially to obtain the modified polyethylene material.

7. The method for preparing the modified polyethylene material as described in claim 6, characterized in that, In step (a), the mixing temperature is 90~100℃, the time is 10~15min, and the rotation speed is 200~300rpm; In step (a), the mass of the first portion of the ethylene-vinyl acetate copolymer is 40-45% of the total mass of the ethylene-vinyl acetate copolymer; The granulation temperature in step (a) is 130~135℃.

8. The method for preparing the modified polyethylene material as described in claim 7, characterized in that, The temperature for the secondary mixing in step (b) is 125~130℃; The temperature of the three mixing steps in step (b) is ≤85℃; The granulation temperature in step (b) is 120~135℃.

9. The method for preparing the modified polyethylene material as described in claim 8, characterized in that, The extrusion temperature in step (c) is 120~140℃; In step (c), the crosslinking temperature is 170~180℃, the pressure is 15~20MPa, and the time is 15~20min.

10. The application of the modified polyethylene material according to any one of claims 1 to 5 in the protective layer of thermally expandable power cables.